Przedszkola Reggio Emilia we Włoszech miejscem rozkwitu dziecięcego potencjału - Jolanta Bonar; Aleksandra Maj (Problemy Wczesnej Edukacji)
The article presents one of the most avant-garde educational experiences for young children in the world. The first preschools in Reggio Emilia (Italy) were established after the Second World War and they have been under the supervision of the municipality for over 45 years. The main initiator and educator of this early childhood practice was Loris Malaguzzi (1920–1994). One of the reasons for this long-lasting project is the readiness of Reggio Emilia educators to cross boundaries, and another is their openness to new ideas and perspectives. They take their inspiration not only from pedagogy, but from philosophy, the exact sciences, architecture, literature, and visual communication as well. Inspired by different ideas and theories, being reflective and inquiring, they interpret and construct their own concepts and theories instead of reproducing them.